International graduate research students: Evolving academic identities - Mukherjee, Agrata; Fernandes, Venesser (Journal of International Students, 2024)
International students are  aspirational and expectant of their learning improving the quality of their life. The stress from academic pressure and acculturative challenges exasperates them from fully experiencing a quality higher educational experience. Despite this, they continuously strive to learn and adjust as they construct their academic identities. While research studies provide several independent perspectives on identity using social, psychological, historical, and political orientations, the current small-scale explorative study focuses on a socio-psychological perspective, discussing the evolution of academic identities of early-career international graduate research (ECIGR) students. This study emerged from the lack of a comprehensive definition of  students’ academic identity and may contribute to this evolving definition. It adopts a case-study approach with semi-structured interviews and applies the situated learning theory.